2017
DOI: 10.1039/c7dt00728k
|View full text |Cite
|
Sign up to set email alerts
|

Probing the local structure of Prussian blue electrodes by 113Cd NMR spectroscopy

Abstract: We demonstrate that 113Cd NMR is a potent technique to monitor the local electronic and structural states of the Prussian blue electrode during Li+ intercalation, providing an atomic-scale insight into the reaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…In previous works, we showed that NMR active nuclei of diamagnetic ions such as 113 Cd could be used as local probe to access accurate information on the local structure and electronic states of paramagnetic cyanide‐based compounds [23] . For example, we showed that 113 Cd NMR was efficient in revealing the electronic state changes occurring upon reversible Li + intercalation in nanoporous CdFe Prussian blue analogues (PBAs) [23c] . This information is made accessible in a M−CN−Cd pair as the changes of electronic/magnetic state on the M ion can be felt by the diamagnetic NMR active Cd(II) ion.…”
Section: Resultsmentioning
confidence: 99%
“…In previous works, we showed that NMR active nuclei of diamagnetic ions such as 113 Cd could be used as local probe to access accurate information on the local structure and electronic states of paramagnetic cyanide‐based compounds [23] . For example, we showed that 113 Cd NMR was efficient in revealing the electronic state changes occurring upon reversible Li + intercalation in nanoporous CdFe Prussian blue analogues (PBAs) [23c] . This information is made accessible in a M−CN−Cd pair as the changes of electronic/magnetic state on the M ion can be felt by the diamagnetic NMR active Cd(II) ion.…”
Section: Resultsmentioning
confidence: 99%
“…[85] The larger negative chemical shift is likely caused by the fact that the more the Fe paramagnetic ions are connected to the intercalation ions, the greater the distribution of the spin density on the nitrogen ions. [86] This also indicates the existence of the designed Fe-N interaction. The obvious 4.1 ppm and weak 3.5 ppm peaks are attributed to physical adsorption of water on the material surface.…”
mentioning
confidence: 81%
“…With advancements in molecular bistable systems, their characterization methods, and various device fabrication techniques and strategies, ,,, the hidden potential of field is being realized and will lead to many groundbreaking findings in the field of molecular devices and nanodevices.…”
Section: Future Outlookmentioning
confidence: 99%